The determining role of reversed austenite in enhancing toughness of a novel ultra-low carbon medium manganese high strength steel. (15th July 2015) - Hu, Jun; Du, Lin-Xiu; Sun, Guo-Sheng; Xie, Hui; Misra, R.D.K.
Abstract : The ultra-low carbon medium Mn steel was subjected to quenching and intercritical tempering process. The 650 °C tempering route led to 15% volume fraction of austenite with combination of high yield strength of 650 MPa, low yield ratio of 0.86, and excellent elongation of ∼31%. The impact energy at −20 °C was enhanced more than twenty times from 10 J to 213 J. The formation of reversed transformation austenite during the intercritical tempering process contributed to the observed superior mechanical properties.